Sradha dan Bhakti Dalam Mencegah Penyalahgunaan Media Sosial - Widiastuti, Ida Ayu Nyoman; Raimahayanti, Ni Made (Metta : Jurnal Ilmu Multidisiplin, 2023)
The development of technology and information is also felt with the existence of smartphones which can make it easier to disseminate information. With just one hand, you can now get information quickly, regardless of distance and time. Social media has actually been around for a long time, but now it has become more advanced and there are many social media options that can be chosen and accessed. However, social media also has a negative impact due to misuse of social media. We can suppress the negative influence of social media abuse by upholding our belief in God Almighty. To prevent the negative influence of social media abuse among society, it is necessary to strengthen and increase Sradha and Bhakti so that they are in accordance with the teachings of Hinduism. This research uses descriptive qualitative research. This social media can be used as a means of modern communication technology, Sradha and Bhakti in Hindu religious teachings can also be applied in preventing misuse of social media and can also be applied in the modern era like today. One religious teaching that can be used to prevent misuse of social media is by applying the teachings of Catur Marga Yoga, which is the path to God. One of the teachings of Bhakti Marga is the path to God with our devotion to Ida Sang Hyang Widhi Wasa. Apart from that, it can also be applied by applying the teachings of Nawa Widha Bhakti or nine ways to show devotion to Ida Sang Hyang Widhi Wasa. Thus, through the application of Sradha and Bhakti it can be used as a way to prevent misuse of social media.